FAKTOR-FAKTOR YANG MEMPENGARUHI PATOGENITAS TRICHOMONAS VAGINALIS - Azahra, Sresta; Susanto, Lisawati (Jurnal Analis Laboratorium Medik, 2023)
Trichomonas vaginalis is a flagellated protozoan parasite that causes trichomoniasis. Trichomoniasis is a non-viral sexually transmitted infection and is found in the human urogenital tract. The interaction between T. vaginalis with the host is very complex and many factors influence the pathogenicity of T. vaginalis. To determine the factors that influence the pathogenicity of Trichomonas vaginalis. Literature review using the Google Scholar database. The search results for articles matched the criteria with the keyword "pathogenicity of Trichomonas vaginalis". Pathogenicity factors include changes in the trophozoite Trichomonas vaginalis to an ameboid form, cellular pathogenicity (attachment of Trichomonas vaginalis to host cells, cytotoxic and hemolytic activity, phagocytosis), interactions with vaginal flora, symbiont contribution with Trichomonas vaginalis, recognition by the host immune system, and evasion host immune system. Pathogenicity factors include changes in the trophozoite Trichomonas vaginalis to an ameboid form, cellular pathogenicity (attachment of Trichomonas vaginalis to host cells, cytotoxic and hemolytic activity, phagocytosis), interactions with vaginal flora, symbiont contribution with Trichomonas vaginalis, recognition by the host immune system, and evasion host immune system.